Comparison of the severity of lower extremity arterial disease in smokers and patients with diabetes using a novel duplex Doppler scoring system - Hiremath, Rudresh (Ultrasonography, 2017)
PURPOSE: The aim of this study was to validate the diagnostic feasibility of a novel scoring system of peripheral arterial disease (PAD) in smokers and patients with diabetes depending on duplex Doppler sonographic features. METHODS: Patients presenting with the symptomatology of PAD were divided into three groups: diabetes only, smoking only, and smokers with diabetes. The patients were clinically examined, a clinical severity score was obtained, and the subjects were categorized into the three extrapolated categories of mild, moderate, and severe. All 106 subjects also underwent a thorough duplex Doppler examination, and various aspects of PAD were assessed and tabulated. These components were used to create a novel duplex Doppler scoring system. Depending on the scores obtained, each individual was categorized as having mild, moderate, or severe illness. The Cohen kappa value was used to assess interobserver agreement between the two scoring systems. RESULTS: Interobserver agreement between the traditional Rutherford clinical scoring system and the newly invented duplex Doppler scoring system showed a kappa value of 0.83, indicating significant agreement between the two scoring systems (P<0.001). CONCLUSION: Duplex Doppler imaging is an effective screening investigation for lower extremity arterial disease, as it not only helps in its diagnosis, but also in the staging and grading of the disease, providing information that can be utilized for future management and treatment planning.